MPCA for flight dynamics parameters determination - Sumida, Ivana Y.; de Campos Velho, Haroldo F.; Luz, Eduardo F.P.; Cruz, Ronaldo V.; Góes, Luiz Carlos S. (Computer Assisted Methods in Engineering and Science, 2014)
Aircraft have become increasingly costly and complex. Military and civil pilots and engineers have used flight simulators in order to increase safety of flight through the training of crew. It is necessary to calibrate the simulation for simulators to have good adherence to reality, that is, to identify the parameters that make the simulation as close as possible to the actual dynamics. After determining these parameters, the simulator will be ready to be used in human resources training or assessing the aircraft. Parameter identification characterizes the aerodynamic performance of the aircraft and can be formulated as a problem optimization. The calibration of a dynamic flight simulator is achieved by a new meta-heuristic called multiple particle collision algorithm (MPCA). Preliminary results show a good performance of the employed approach.